(3GdeONd GdeajO aj Mce GdehGdjOs - (3jMji Hf eMeO Hf CHj GdTcQ, eMjj GdOjf, CHh GdaJM, hjYQa HGdMcje GdeZQHj , GHf CHj GdoqTrcQ , J fMh (B680 (3g`s
(3ChdgG (B:s
(3REfi bO QJHJ gPg GdebGdg ai cjajg GdMce Ydi GdeSGFd GdeNJUg HCMhGd GdeSGFd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B90 - (3U(B181 :s
(3jMJhi ai BNQg Ydi HYV GdQShe hGdLOGhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B868 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B95 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs